Polar switching in trialkylbenzene-1,3,5-tricarboxamides - Fitié, Carel F. C.; Roelofs, W. S. Christian; Magusin, Pieter C. M. M.; Wübbenhorst, Michael; Kemerink, Martijn; Sijbesma, Rint P. (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2012)
The hydrogen-bonded hexagonal columnar LC (Colhd) phases formed by benzene-1,3,5-tricarboxamide (BTA) derivatives can be aligned uniformly by an electric field and display switching behavior with a high remnant polarization. The polar switching in three symmetrically substituted BTAs with alkyl chains varying in length between 6 and 18 carbon atoms (C6, C10, and C18) was investigated by electro-optical switching experiments, dielectric relaxation spectroscopy (DRS), and solid-state NMR. The goal was to characterize ferroelectric properties of BTA-based columnar LCs, which display a macroscopic axial dipole moment due to the head-to-tail stacking of hydrogen-bonded amides. The Colhd phase of all three BTAs can be aligned uniformly by a dc field ∼30 V/μm. Moreover, C10 and C18 display extrinsic polar switching characterized by a remnant polarization and coercive field of 1-2 μC/cm2 and 20-30 V/μm, respectively. In the absence of an external field, the polarization is lost in 1-1000 s, depending on device details and temperature. DRS revealed a columnar glass transition in the low-temperature region of the LC phase related to collective vibrations in the hydrogen-bonded columns that freeze out below 41-54 °C. At higher temperatures, a relaxation process is present originating from the collective reorientation of amide groups along the column axis (inversion of the macrodipole). Matching activation energies suggest that the molecular mechanism underlying the polar switching and the R-processes is identical. These results illustrate that LC phases based on BTAs offer the unique possibility to integrate polarization with other functionalities in a single nanostructured material.